Gender-Based Violence and the Implementation of the Sexual Violence Crime Law in Indonesia - Indah Sri Utari; Ridwan Arifin; Sergi Fernandez Alejandro (The Indonesian Journal of Feminist Legal Studies, 2026)
Gender-based violence remains a pervasive human rights issue in Indonesia, despite recent legal reforms aimed at strengthening victim protection and ensuring access to justice. The enactment of the Sexual Violence Crime Law (Law No. 12 of 2022) represents a significant milestone in Indonesia’s legal framework for addressing sexual violence. This article examines the implementation of the law and evaluates its effectiveness in responding to gender-based violence from a feminist legal perspective. Using a normative juridical approach complemented by qualitative analysis of statutory regulations, policy documents, and reported cases, the study investigates the extent to which the law has transformed institutional responses to victims. The findings reveal that while the legislation introduces comprehensive definitions of sexual violence, victim-centered protection mechanisms, and broader state obligations, substantial implementation challenges persist. These include limited institutional capacity, inadequate law enforcement training, socio-cultural stigmatization of victims, and uneven coordination among relevant agencies. The study further identifies tensions between progressive legal norms and patriarchal social structures that continue to shape legal practices and public perceptions. The article argues that legal reform alone is insufficient to eradicate gender-based violence without parallel institutional, cultural, and educational transformations. By assessing the early implementation of the Sexual Violence Crime Law, this study contributes to ongoing debates on feminist legal reform and offers policy recommendations for strengthening victim protection and improving access to justice in Indonesia. The findings also provide insights for other jurisdictions seeking to develop comprehensive legal responses to sexual violence within complex socio-cultural contexts.